2021
DOI: 10.1007/s10482-021-01623-6
|View full text |Cite
|
Sign up to set email alerts
|

Sphingobacterium pedocola sp. nov. a novel halotolerant bacterium isolated from agricultural soil

Abstract: A Gram-reaction-negative halotolerant bacterial strain, designated Ka21T, was isolated from agricultural soil and characterised using a polyphasic approach to determine its taxonomic position. On the basis of 16S rRNA gene sequence analysis, highest similarity was found with Sphingobacterium alkalisoli Y3L14T (96.72%). Cells were observed to be aerobic, non-motile rods. The isolate was found to be able to grow between 0 and 10% of NaCl concentration. The assembled genome of strain Ka21T has a total length of 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…While the highest NaCl concentration tested in this study reached only 1.05% (4× artificial sweat) and is not considered a high salt concentration, many skin microorganisms are highly halotolerant and capable of withstanding drastic changes in osmotic pressure, including Staphylococcus and Corynebacterium species ( 55 61 ). In addition, nearly all of the other genera in this study have been identified as being halotolerant in previous reports ( 62 67 ).…”
Section: Discussionsupporting
confidence: 69%
“…While the highest NaCl concentration tested in this study reached only 1.05% (4× artificial sweat) and is not considered a high salt concentration, many skin microorganisms are highly halotolerant and capable of withstanding drastic changes in osmotic pressure, including Staphylococcus and Corynebacterium species ( 55 61 ). In addition, nearly all of the other genera in this study have been identified as being halotolerant in previous reports ( 62 67 ).…”
Section: Discussionsupporting
confidence: 69%
“…While the highest NaCl concentration tested in this study only reached 1.05% (4X artificial sweat) and is not considered a high salt concentration, many skin microorganisms are highly halotolerant and capable of withstanding drastic changes in osmotic pressure, including Staphylococcus and Corynebacterium species (4753). In addition, nearly all other genera in this study have reports of species being identified as halotolerant (5459).…”
Section: Discussionmentioning
confidence: 85%
“…sunkii in 2012 [12]. This name was effectively and validly published in the IJSEM in accordance with the ICNP [5,13]. However, the subspecific epithet 'sunkii' in fact had already been used for the specific epithet of the name of another species within the same genus, viz.…”
Section: Nomenclatural Status Of the Name Lactobacillus Delbrueckii S...mentioning
confidence: 99%
“…Mycobacterium bovis Karlson andLessel 1970 (Approved Lists 1980) [10,11]. According to Rule 12b of the ICNP, no specific or subspecific epithets within the same genus may be the same if based on different types [5]. Rule 53 also stipulates that an epithet is illegitimate if it duplicates a specific or subspecific epithet previously validly published for a species or subspecies of the same genus and if this species or subspecies is a different bacterium with a name based upon another type.…”
Section: Nomenclatural Status Of the Name Mycobacterium Chelonae Subs...mentioning
confidence: 99%
See 1 more Smart Citation